Real wage cyclicality of newly hired workers - Heiko Stüber (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2013)
Several recent marcoeconomic models rely on rigid wages. Especially wage rigidity of newly hired workers seems to play a crucial role, since the decision of opening a vacancy or not is mainly influenced by their real wages. However, so far little empirical evidence exists on how real wages of newly hired workers react to business cycle conditions. This paper aims at filling this gap for a large economy, namely Germany, by analyzing the cyclical behavior or real wages of newly hired workers while controlling for cyclical up- and downgrading in employer/employee matches. For the analysis two endogenous variables are used: either the typical (e.g. modal) real wages paid to entrants into particular jobs of particular firms or entrants' individual real wages. The results show that entry-wages are not rigid, but considerably respond to business cycle conditions. This finding strengthens Pissarides' (2009) dismissal of theories based on cyclically rigid hiring wages. Furthermore, I show that the procyclicality of the employment / population ratio is (nearly) identical to the procyclicality of real entry-wages.
urn:nbn:de:bsz:100-opus-8025
Keywords: E24; E32; J31; 330; real wage cyclicality; entry-wages; search and matching model